2020
DOI: 10.3390/ijms21239059
|View full text |Cite
|
Sign up to set email alerts
|

Exercise and the Cisd2 Prolongevity Gene: Two Promising Strategies to Delay the Aging of Skeletal Muscle

Abstract: Aging is an evolutionally conserved process that limits life activity. Cellular aging is the result of accumulated genetic damage, epigenetic damage and molecular exhaustion, as well as altered inter-cellular communication; these lead to impaired organ function and increased vulnerability to death. Skeletal muscle constitutes ~40% of the human body’s mass. In addition to maintaining skeletal structure and allowing locomotion, which enables essential daily activities to be completed, skeletal muscle also plays … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 92 publications
0
11
0
Order By: Relevance
“…In our preliminary test, an enhancement of Cisd2 gene expression in HEK293T cells was presented in GKK2 treatment but not in the GKS6 group (Figure S2). A persistent level of Cisd2 protected mitochondrial dysregulation and reduced DNA damage caused by oxidative stress; in addition, Cisd2 was involved in calcium homeostasis through the regulation of the calcium channels located on the endoplasmic reticulum and mitochondrial outer membranes [28][29][30]. ese affections maintain a better physical function in skeletal muscle, liver, and heart [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…In our preliminary test, an enhancement of Cisd2 gene expression in HEK293T cells was presented in GKK2 treatment but not in the GKS6 group (Figure S2). A persistent level of Cisd2 protected mitochondrial dysregulation and reduced DNA damage caused by oxidative stress; in addition, Cisd2 was involved in calcium homeostasis through the regulation of the calcium channels located on the endoplasmic reticulum and mitochondrial outer membranes [28][29][30]. ese affections maintain a better physical function in skeletal muscle, liver, and heart [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, some interventions seem to be associated with enhanced Cisd2 expression in mammals. For example, one of our recent studies has demonstrated that treadmill exercise for 56 days is able to significantly enhances Cisd2 expression using a Cisd2-luciferase reporter mouse model [ 34 ]. Moreover, voluntary exercise for four weeks is able to increase Cisd2 protein levels in the skeletal muscle and white adipose tissue of mice [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated that exercising initiated at an age when deleterious alterations in the heart have already begun can attenuate cardiac fibrosis and collagen crosslinking that occur when an individual reaches an advanced age; these are important contributors to morbidity and mortality at an old age [ 27 , 28 ]. A human study also demonstrated that lifelong endurance training can preserve cardiac function at a level similar to that of young subjects, although the mechanism remains unknown [ 29 ].…”
Section: Discussionmentioning
confidence: 99%